1970
DOI: 10.3329/jom.v8i1.1374
|View full text |Cite
|
Sign up to set email alerts
|

Jaundice in Pediatric Visceral Leishmaniasis (Kala-azar) Patients

Abstract: Visceral leishmaniasis (Kala-azar) is endemic in many countries including Bangladesh. Clinical presentation of visceral leishmaniasis in children and adult may vary and at time may simulate many tropical and hepatobilliary diseases. Jaundice and ascites is not common in some patients. In this series of eleven cases Jaundice, splenomegaly, hepatomegaly and ascites are present in 55%, 100%, 91%, 27% of cases respectively. So, Kala-azar should be kept in mind while dealing with cases of many such clinical finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 1 publication
1
5
0
Order By: Relevance
“…[14][15][16][17][18][19] Similarly, studies conducted in India and Bangladesh also reported abnormally high liver inflammatory enzymes like ALT, AST, and ALP in VL patients. 6,20 This may be attributed to the levels of particular circulating cytokines during the inflammatory processes observed in active VL disease could be a determinant and consequence of severe liver disease. 17 The liver function alteration might be due to hepatomegaly and the generation of immune complex in VL patients.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16][17][18][19] Similarly, studies conducted in India and Bangladesh also reported abnormally high liver inflammatory enzymes like ALT, AST, and ALP in VL patients. 6,20 This may be attributed to the levels of particular circulating cytokines during the inflammatory processes observed in active VL disease could be a determinant and consequence of severe liver disease. 17 The liver function alteration might be due to hepatomegaly and the generation of immune complex in VL patients.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the patient presented jaundice (++/4). Although jaundice and ascites are considered rare features in VL 20 , other studies have demonstrated that different degrees of jaundice has been observed as an usual clinical presentation, particularly in children 21 , 22 .…”
Section: Discussionmentioning
confidence: 95%
“…In a recent Bangladeshi study, it is found that initial diagnosis of chronic liver disease was made in 36% of the patient with visceral leishmaniasis & same study also mentions that 9% of Kala-azar patient was initially thought to have congenital hemolytic anaemia. 4 In India, multiple cases are reported where visceral leishmaniasis was mistaken for chronic liver disease & treatment was delayed which ultimately proved to be fatal. 5,6 In these cases, correct diagnosis was delayed mainly due to absence of features characteristic of visceral leishmaniasis, such as fever.…”
Section: Discussionmentioning
confidence: 99%
“…Kala-azar often involves the liver due to effect of LD body itself or immunological response against it leading to altered biochemistry of liver. 4 We investigated thoroughly pursuing both lines of diagnoses. Upper GI endoscopy &fibroscan of liver were normal.…”
Section: Discussionmentioning
confidence: 99%